A randomised controlled trial comparing the effects of directive and non-directive parenting programmes as a universal prevention programme. Issue 1 (21st March 2016) - Chan, Stanley; Leung, Cynthia; Sanders, Matthew
Abstract : Purpose: – The purpose of this paper is to compare the effectiveness of directive programmes led by professionals where parents were taught specific parenting knowledge and strategies (Triple P – Positive Parenting Program) and non-directive parenting programmes in the form of mutual-aid support group as a universal prevention programme. Design/methodology/approach: – This study employed a randomised controlled trial design. Participants included 92 Hong Kong Chinese parents with preschool children recruited from eight kindergartens and a local church. They were randomised into Group Triple P, non-directive group and control group. They completed measures on their perception of child behaviour problems and their parental stress before and after intervention. Findings: – At post-intervention, results indicated significantly greater decrease in child disruptive behaviours among participants in the Triple P group than those in the non-directive group and control group while no significant group difference was found between the latter two groups. No significant difference was found in post-intervention parental stress level among the three groups. Originality/value: – This study provides empirical evidence to demonstrate the effectiveness of a directive parenting programme vs a non-directive one.